A Low‐Cost Metal‐Free Photocatalyst Based on Black Phosphorus - Wen, Min (Adv Sci (Weinh), 2018)
An efficient metal‐free photocatalyst composed of black phosphorus (BP) and graphitic carbon nitride (CN) is prepared on a large scale by ball milling. Using economical urea and red phosphorus (RP) as the raw materials, the estimated materials cost of BP/CN is 0.235 Euro per gram. The BP/CN heterostructure shows efficient charge separation and possesses abundant active sites, giving rise to excellent photocatalytic H(2) evolution and rhodamine B (RhB) degradation efficiency. Without using a co‐catalyst, the metal‐free BP/CN emits H(2) consistently at a rate as large as 786 µmol h(−1) g(−1) and RhB is decomposed in merely 25 min during visible‐light irradiation. The corresponding electron/hole transfer and catalytic mechanisms are analyzed and described. The efficient metal‐free catalyst is promising in visible‐light photocatalysis and the simple ball‐milling synthetic method can be readily scaled up.